Optical properties of carbon nanoparticles derived from mung bean - Quang, Ngô Khoa; Nguyễn, Thị Sương; Phan, Thị Khánh Linh; Lê, Xuân Diễm Ngọc (Hue University Journal of Science: Natural Science, 2022)
In this study, we synthesized carbon nanodots (CDs) from mung bean with the hydrothermal method. The average diameter of the CDs is 13.8 nm. The UV-vis absorption spectrum shows a characteristic peak at l = 280 nm, corresponding to the n → p* transition in the C=O bonds. The obtained CDs exhibit a broad emission spectrum ranging from 320 to 460 nm under different excitation wavelengths. Furthermore, by using the comparative method and quinine sulfate as a reference, we obtained a quantum yield of 12.18%. This quantum yield is relatively high compared with that of other precursors.